Abrasive wear behavior of various reinforced AA6061 matrix composites produced with hot pressing process: A comparative study: Abriebverhalten von verschiedenen durch Heißpressen hergestellten verstärkten AA6061‐Matrix‐Kompositen: Eine Vergleichsstudie. Issue 6 (June 2017) - Ismail, O.
Abstract: The effects of various reinforcements (boron carbide ‐silicon carbide‐alumina) with constant volume fraction (20 %) on the abrasive wear properties of AA6061 matrix composites produced with hot pressing process were investigated. The wear tests were carried out using a pin‐on‐disk wear tester by sliding at sliding speeds of 1.2 m/s against silicon carbide paper. Applied normal loads have 5, 10 and 15 N magnitude at room temperature. The wear morphologies of the worn surfaces were analyzed using a scanning electron microscope in order to examine the wear characteristics and to investigate the wear mechanisms. The effects of reinforcement type on the wear behavior of AA6061 matrix composites were observed. Results exhibited that the optimum wear resistance obtained with the boron carbide reinforced composite parts. All reinforced samples showed better wear resistance compared to as‐received samples in all the studied conditions. Scanning electron microscope characterization showed that test specimens have complex combination of wear mechanisms on the worn surface.